A Preliminary Investigation of NSCL/P Plasma and Urine in Guizhou Province in China Using NMR-Based Metabonomics. (September 2013) - Lei, Huang Guang; Hong, Luo; Kun, Song Ju; Hai, Yin Xin; Dong, Wang Ya; Ke, Zhao; Ping, Xu; Hao, Chen
Objective: To assess the feasibility of metabonomics in clinical studies. This is a pilot study introducing nuclear magnetic resonance (NMR)–based metabonomics to elucidate and compare the metabolism of patients with nonsyndromic cleft lip and/or palate (NSCL/P) and children without orofacial clefts. Methods: High-resolution 1 H NMR spectroscopy was performed on plasma and urine samples obtained from NSCL/P and healthy children. The 1 H NMR spectra were further analyzed with principal component analysis. Results: Compared to the control group, the level of low-molecular-weight metabolites in plasma such as asparagine was higher in NSCL/P patients, while arginine, lysine, acetate, lactate, proline, glutamine, pyruvate, creatinine, choline, and β-glucose were lower. The carnitine, citrate, and formate excretion in urine appeared to be higher in the healthy children, while the NSCL/P group excreted higher concentrations of aspartic acid and phenylalanine in urine. Conclusion: The present study clearly demonstrated the great potential of NMR-based metabonomics in elucidating NSCL/P plasma metabolism and the possible application of this technology in clinical diagnosis and screening.